Lactobacillus plantarum ZS2058 and Lactobacillus rhamnosus GG Use Different Mechanisms to Prevent Salmonella Infection in vivo - Liu, Junsheng; Gu, Zhennan; Song, Fanfen; Zhang, Hao; Zhao, Jianxin; Chen, Wei (Frontiers in Microbiology, 2019)
Pathogen-induced infectious diseases pose great threats to public health. Accordingly, many studies have investigated effective strategies targeting pathogenic infections. We previously reported the preventive effects of Lactobacillus plantarum ZS2058 (ZS2058) and L. rhamnosus GG (LGG) against Salmonella spp. in a murine model. Here, we compared the mechanisms underlying the preventive effects of these Lactobacillus strains in vivo. Notably, reduced C-reactive protein levels were observed with both ZS2058 and LGG, which suggests abrogated anti-infection and inflammatory responses. ZS2058 more efficiently reduced the pathogenicity of Salmonella by increasing the level of propionic acid in feces and production of mucin 2 in the mouse colon and activity through the interleukin (IL)-23/IL-22 and IL-23/IL-17 pathways. Meanwhile, LGG more strongly alleviated gut inflammation, as indicated by changes in the levels of tissue necrosis factor (TNF)-α, IL-10 and myeloperoxidase (MPO) in infected mice. Moreover, both ZS2058 and LGG restored the levels of interferon (INF)-γ, a cytokine suppressed by Salmonella, albeit through different pathways. Our results demonstrate that ZS2058 and LGG prevent Salmonella infection via different mechanisms.